1997
DOI: 10.1200/jco.1997.15.3.1013
|View full text |Cite
|
Sign up to set email alerts
|

Phase III trial of androgen suppression using goserelin in unfavorable-prognosis carcinoma of the prostate treated with definitive radiotherapy: report of Radiation Therapy Oncology Group Protocol 85-31.

Abstract: Application of androgen suppression as an adjuvant to definitive radiotherapy has been associated with a highly significant improvement in local control and freedom from disease progression. At this point, with a median follow-up time of 4.5 years, a significant improvement in survival has been observed only in patients with centrally reviewed tumors with a Gleason score of 8 to 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
228
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(238 citation statements)
references
References 20 publications
3
228
0
7
Order By: Relevance
“…Although the final choice of treatment modalities belonged to patients, many patients with locally advanced cancer underwent XRT in our series, as shown in Table 1. Since phase III studies with large cohorts demonstrated that combination therapy with radiation and hormone improved the survival of patients with locally advanced prostate cancer compared with radiation monotherapy, 14,15 we routinely used neoadjuvant LHRH analogue therapy prior to radiation therapy. Our patients received only 66 Gy of radiation, since conformal radiation is not available in our institute.…”
Section: Discussionmentioning
confidence: 99%
“…Although the final choice of treatment modalities belonged to patients, many patients with locally advanced cancer underwent XRT in our series, as shown in Table 1. Since phase III studies with large cohorts demonstrated that combination therapy with radiation and hormone improved the survival of patients with locally advanced prostate cancer compared with radiation monotherapy, 14,15 we routinely used neoadjuvant LHRH analogue therapy prior to radiation therapy. Our patients received only 66 Gy of radiation, since conformal radiation is not available in our institute.…”
Section: Discussionmentioning
confidence: 99%
“…As early as the 1960s, cytoreductive hormonal therapy was added to radiation therapy to reduce tumour burden and provide a more favourable geometry for external irradiation 57 . Recently, three separate randomized trials have shown the beneficial effects of combining androgen-ablation therapy with radiation, improving times of relapsefree and overall survival [58][59][60] ; also, the incorporation of androgen ablation before, during and after external-beam radiation has become the standard of care.…”
Section: Radiation Therapymentioning
confidence: 99%
“…In addition, patients with Gleason 8 -10 tumors had statistically significant higher overall survival rates when treated with androgen ablation. 11 A similar randomized prospective trial by Bolla and colleagues in patients with predominantly clinical stage T3 disease also showed a significant survival benefit to a 3-y course of goserelin which began at the start of EBRT. 12 A third prospective trial open to both low-and high-risk patients by Laverdiere and colleagues 10 randomized patients undergoing EBRT into three groups: a control group with no hormonal manipulation, a group which underwent 3 months of combined androgen ablation prior to EBRT, and a third group which underwent androgen ablation 3 months before, during, and 6 months after EBRT.…”
Section: Discussionmentioning
confidence: 86%
“…Our combined EBRT þ BT protocol is outlined in Figure 1. Due to evidence that neoadjuvant hormonal deprivation enhances disease-free survival in EBRT for locally advanced prostate cancer, 11,12 all patients underwent 8 months of combined androgen ablation with an LHRH (luteinizing hormone releasing hormone) agonist (leuprolide) and oral antiandrogen (bicalutamide or flutamide). External beam therapy of 40 -45Gy over 6 weeks began 2 -3 months after initiation of androgen blockade.…”
Section: Brachytherapy Techniquesmentioning
confidence: 99%